The Implementation of Islamic Family Law in Indonesia A Study on the Application of the Marriage Law and the Compilation of Islamic Law - Abdul Wahid (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Islamic family law is an essential component of the Islamic legal system that regulates personal matters such as marriage, divorce, inheritance, and guardianship. In Indonesia, the implementation of Islamic family law gains a strong legal foundation through Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI), enacted under Presidential Instruction Number 1 of 1991. This article aims to examine the application of Islamic family law in Indonesia, with a focus on the synchronization between normative provisions in Islamic law and their implementation within the religious court system. This study employs a qualitative method with a normative juridical approach, analyzing legislation, court decisions, and Islamic legal literature. The findings indicate that although Islamic family law has been formally institutionalized, challenges remain in law enforcement, public awareness, and differences in interpretation between legal texts and social practices. Continuous reform and harmonization are needed to ensure that Islamic family law is applied in a fair, relevant, and contextually appropriate manner in Indonesia.